Life Cycle Sustainability Assessment (LCSA): A comprehensive overview of existing integrated approaches to LCA, S-LCA, and LCC - Bruno, Alba; Menichini, Tamara; Silvestri, Luca (European Journal of Sustainable Development, 2025)
Life Cycle Sustainability Assessment (LCSA) is emerging as a robust framework for integrated impact assessment across environmental, social, and economic dimensions, addressing the growing complexity of today’s sustainability challenges. It consists of the combination of three different analyses: Life Cycle Assessment (LCA), Life Cycle Costing (LCC), and Social LCA (s-LCA). These methodologies have different technical maturity and specific peculiarities in the outcome. Hence, it is necessary to integrate different aspects of various techniques, combining both quantitative and qualitative data. The aim of this study is to provide an accurate and accessible overview of the various possible approaches for implementing a rigorous and integrated LCSA. Furthermore, the authors propose a clear and comprehensive classification of the major methods. Through a rigorous review process, a total of 66 papers were selected and analyzed, each simultaneously applying the three components of LCSA. The various integration methods were then aggregated into different categories, which are: (i) sequential analysis of LCA, LCC, s-LCA; (ii) graphical representation approaches; (iii) integration based on Multi-Criteria Decision Analysis (MCDA); and (iv) tailored ranking methods and metrics. Keywords: Life Cycle Sustainability Assessment; Life Cycle Assessment; Life Cycle Costing; Social Life Cycle Assessment